2015
DOI: 10.1080/1357650x.2015.1117095
|View full text |Cite
|
Sign up to set email alerts
|

A leftward bias however you look at it: Revisiting the emotional chimeric face task as a tool for measuring emotion lateralization

Abstract: (2016) 'A leftward bias however you look at it : revisiting the emotional chimeric face task as a tool for measuring emotion lateralization.', Laterality., 21 (4-6). pp. 643-661. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
42
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 66 publications
9
42
1
Order By: Relevance
“…These results are in line with findings of a meta-analysis which suggested that free-viewing laterality tasks, such as the ECFT task, are reliable and easy to administer tool for the assessment of RH integrity (Voyer, Voyer, & Tramonte, 2012). The LVF/RH bias consistently found in ECFT does not appear to differ according to stimulus valence (Bourne, 2010(Bourne, , 2011Christman & Hackworth, 1993;Innes, Burt, Birch, & Hausmann, 2016;Workman, Peters, & Taylor, 2000). Given also that studies consistently report left hemiface biases using only expressions of happiness (Bourne & Gray, 2011;Levy et al, 1983), this is taken as strong evidence against the Valence-Specific Hypotheses in favour of the RH Hypothesis.…”
Section: Introductionsupporting
confidence: 89%
“…These results are in line with findings of a meta-analysis which suggested that free-viewing laterality tasks, such as the ECFT task, are reliable and easy to administer tool for the assessment of RH integrity (Voyer, Voyer, & Tramonte, 2012). The LVF/RH bias consistently found in ECFT does not appear to differ according to stimulus valence (Bourne, 2010(Bourne, , 2011Christman & Hackworth, 1993;Innes, Burt, Birch, & Hausmann, 2016;Workman, Peters, & Taylor, 2000). Given also that studies consistently report left hemiface biases using only expressions of happiness (Bourne & Gray, 2011;Levy et al, 1983), this is taken as strong evidence against the Valence-Specific Hypotheses in favour of the RH Hypothesis.…”
Section: Introductionsupporting
confidence: 89%
“…As in previous bubbles (e.g., Dupuis-Roy et al, 2009, 2018Gosselin & Schyns, 2001;Ince et al, 2016), eye-tracking (Butler et al, 2005), and chimeric faces studies (Butler et al, 2005;Innes, Burt, Birch, & Hausmann, 2016), there appeared to be a slight bias for the use of the left-eye region from the observer's perspective compared with the right-eye region (see Figure 2a). We showed that this bias is statistically significant by averaging z scores in two regions of interest (ROI)-the right-eye and the left-eye anatomically defined ROIs-for each individual unsmoothed CI and compared average ROI scores with a two-tailed paired t test (M and 3).…”
Section: Average Use Of Informationsupporting
confidence: 71%
“…Single amygdala neurons respond to facial emotions [23], in particular expressions of the eye region [24]. Whereas cortical face processing [25] and its emotion modulation [26] appear preferentially lateralized to the right hemisphere, the lateralization of subcortical emotion effects is still unclear.…”
Section: Neural Systems For Perceiving Emotionsmentioning
confidence: 99%